Stereoselective synthesis of (2S,7S)-7-(4-phenoxymethyl)2-(1-N-hydroxyureidyl-3-butyn-4-yl)oxepane: a potential anti-asthmatic drug candidate - Gurjar, M. K.; Rao, B. V.; Krishna, L. M.; Chorghade, Mukund S.; Ley, S. V. (Tetrahedron-Asymmetry, 2005)
We have achieved a short, efficient stereoselective synthesis of 7-membered oxepane derivatives with potential against asthma. Highlights of our synthetic strategy are regioselective oxidation of a hydroxyl group and efficient ring closure of an open chain aldehyde to a 2-benzenesulfonyl oxepane derivative with PhSO2H. Surprisingly the cis-isomer showed better activity than the traps-isomer. (C) 2005 Elsevier Ltd. All rights reserved.

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Syntheis of unusual tricyclic ring systems of biological interest - Mohapatra, Debendra K.; Maity, Pradip K.; Chorghade, Mukund S.; Gurjar, Mukund K. (Heterocycles, 2007)
We describe a new synthesis of tricyclic scaffolds that incorporate a fusion of triazole with 1,4-benzodiazepine utilizing intramolecular ``click'' chemistry.
Keywords: 1; 2; 3-Triazole; 4-benzodiazepine; Click chemistry; nitrogen rich polycyclic hetero-system; privileged structure

Synthesis of the C19-C34 segment of amphidinolide C - Mohapatra, Debendra K.; Rahaman, Hasibur; Chorghade, Mukund S.; Gurjar, Mukund K. (Synlett, 2007)
The synthesis of the C19-C34 segment of amphidinolide C is described. The key steps include the Mioskowski's Lewis acid catalyzed epoxide opening with the alcohol, ring-closing metathesis, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide C; Cytotoxic; Nozaki-Hiyama-Kishi coupling; Ring-closing metathesis; Wittig reaction

Short total synthesis of (+)-cryptocarya diacetate - Gurjar, Mukund K.; Raghupathi, Neelarapu; Chorghade, Mukund S. (Heterocycles, 2009)
A short synthesis of (+)-cryptocarya diacetate was achieved by employing three component linchpin coupling, diastereoselective reduction of beta-hydroxyketone, and Z-selective HWE reaction as key transformations.
Keywords: Brook Rearrangement; cryptocarya diacetate; Diastereoselective Reduction; Horner-Wadswarth-Emmons Reaction; Linchpin coupling

Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis